2018
DOI: 10.1097/mpg.0000000000001759
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐TNFα Treatment in Children and Adolescents With Combined Inflammatory Bowel Disease and Autoimmune Liver Disease

Abstract: IBD in patients with AILD can be aggressive, requiring escalation to anti-TNFα or switching to other biologics. In this series, anti-TNFα did not impair liver function and improved gut disease in most of the patients, indicating that it can be beneficial and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Another single-center retrospective analysis in 11 pediatric and adolescent patients with IBD and autoimmune liver disease included 2 patients with type 1 AIH and 9 with AIH-PSC overlap. (434) Infliximab (5 mg/kg) was infused to treat the IBD, and 3 patients were later treated with adalimumab after infliximab intolerance or failure. The IBD improved in most patients, and liver enzymes improved in 5.…”
Section: Very Lowmentioning
confidence: 99%
“…Another single-center retrospective analysis in 11 pediatric and adolescent patients with IBD and autoimmune liver disease included 2 patients with type 1 AIH and 9 with AIH-PSC overlap. (434) Infliximab (5 mg/kg) was infused to treat the IBD, and 3 patients were later treated with adalimumab after infliximab intolerance or failure. The IBD improved in most patients, and liver enzymes improved in 5.…”
Section: Very Lowmentioning
confidence: 99%
“…Infliximab has been used as rescue therapy in patients with difficult‐to‐treat AIH; early experience demonstrated reduced inflammation; however, high rates of infectious complications were reported 112‐114 . However, a retrospective report of 11 paediatric cases with concomitant autoimmune liver disease (two with AIH and nine with autoimmune sclerosing cholangitis) treated with anti‐TNF therapy for severe inflammatory bowel disease demonstrated stable or improved liver function tests and only a single infective complication of asymptomatic cytomegalovirus viraemia 115 . There are concerns regarding idiosyncratic hepatotoxicity with anti‐TNF therapy and the impact of this on patients with already impaired liver function needs to be carefully considered.…”
Section: Novel Therapies Undergoing Clinical Assessment In Aihmentioning
confidence: 99%
“…In 2 patients long-term infliximab treatment for 3-10 years permitted sustained remission without losing drug efficacy or causing infectious complications. Furthermore, Nedelkopoulou et al [133] reported improvement in liver function in 5 out of 8 children treated with infliximab for inflammatory bowel disease and concurrent AIH or AIH/PSC-overlap and no deterioration in the remaining 3. One study on etanercept in patients with both, rheumatic arthritis and AIH, reported biochemical and histological response in all 7 patients [134].…”
Section: Infliximabmentioning
confidence: 99%